Estimation of land-based emissions during container terminal operations in the Ambarlı Port, Turkey. (August 2022) - Kara, Gökhan; Emecen Kara, Esma Gül; Okşaş, Olgay
Many types of mobile vehicles are used simultaneously in container terminal operations. Because most of these mobile vehicles have diesel engines, they emit a significant amount of pollutant emissions into the atmosphere during their operation. They are considered as land-based mobile emission sources (MobES) and should be included in the total port emission inventory. The emission inventory is a basic requirement in developing an environmental management strategy to improve emission control. In this context, this study aims to estimate the emission inventories of mobile vehicles used in terminal operations in the Ambarlı container ports located in the city of Istanbul, which is one of the most populous cities in the world. In this respect, the amounts of the emissions of all the container handling equipment with diesel engines in the port areas, including external trucks delivering/receiving containers to/from the port were estimated using an activity-based method. It has been found that approximately 42.39% of the total CO2 emission is owing to terminal tractors and the total annual CO2 value per TEU (Twenty-foot Equivalent Unit) of MobES is 0.01259 tons. The CO2 value per TEU can serve as a CO2 emission performance indicator for land-based MobES in process of the evaluation of emission inventories in container ports.